Towing Norms through the American Dream - Pavel Jelnov (Institute of Labor Economics (IZA), 2023)
This paper takes advantage of a natural experiment, in which Soviet Jewish immigrants were quasi-randomly allocated of to the U.S. and Israel. I find that young women who immigrated as children follow similar fertility profiles in the two host countries. In Israel, they are also similar to native-born women by exercising almost no selection into motherhood and postnatal labor force participation. By contrast, and away from native-born American women, immigrants to the U.S. either combine family and career or become low-educated non-working mothers. This non-trivial segregation arises from a combination of the American Dream with origin-determined fertility norms.
Keywords: J13; J61; 330; immigration; Soviet Jews; female labor force participation; immigrant fertility